Epigenetic control in thyroid cancer: mechanisms and clinical perspective - Jiahui Zhang; Shengkai Zheng; Ruiwang Xie; Junsi Zhang; Xiangjin Chen; Sunwang Xu (Cell Death Discovery)
Abstract Epigenetic regulation plays a key role in the progression, proliferation, and dedifferentiation of thyroid cancer. Epigenetic control occurs at multiple levels, including DNA methylation, RNA modification, histone modification, chromatin remodeling, and chromatin accessibility. Genetic alterations in chromatin regulators are commonly observed in thyroid cancer, which includes papillary thyroid carcinoma (PTC), medullary thyroid carcinoma (MTC), anaplastic thyroid carcinoma (ATC), and follicular thyroid carcinoma (FTC). These cancers exhibit distinct characteristics in terms of genetics, biology, and clinical presentation. Therefore, we review the disease biology driven by changes in chromatin pathways in thyroid cancer. Specifically, we summarize examples of epigenetic dysregulation at each level, with mechanisms involving alterations in enzymes regulating DNA methylation, RNA modification and posttranslational modifications of histones, as well as the loss or fusion of subunits involved in chromatin remodeling and chromatin accessibility. Finally, on the basis of clinical applications, we review the current and potential future approaches for thyroid cancer treatment.